EFEKTIVITAS DAN PERBANDINGAN STRATEGI PEMBELAJARAN TERHADAP KEMAMPUAN MEMBACA PEMAHAMAN SISWA SEKOLAH DASAR: STUDI LITERATUR - Chindytia; Goreti Rini Kristiantari, Maria; Kadek Eny Wahyu Marsanda, Ni; Ketut Ari Diani Putri, Ni; Werdi Guna Sedana Putra, Kadek (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Reading comprehension skills of elementary school students in Indonesia are still relatively low, as indicated by the results of the Programme for International Student Assessment (PISA), which remain below the international average. This condition highlights the need for effective instructional strategies to improve students’ reading comprehension. This study aims to analyze and compare the effectiveness of various instructional strategies in enhancing reading comprehension skills among elementary school students. The method used in this study is a literature review by examining relevant scholarly sources, including journals, books, and previous research findings. The results show that the SQ3R strategy is effective in developing systematic comprehension, Cooperative Integrated Reading and Composition (CIRC) improves understanding through collaborative learning, mind mapping facilitates the organization of information visually, and Problem Based Learning (PBL) enhances critical thinking through problem-solving activities. Each strategy has its own strengths and limitations; therefore, its implementation should be adjusted to students’ characteristics and learning objectives. It is recommended that teachers combine various instructional strategies and utilize diverse learning media to optimize students’ reading comprehension skills.